Investigating JEEM empirically: A story of co-authorship and collaboration - Michael Schymura; Andreas Löschel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
We examine the incidence and extent of co-authorship and intellectual collaboration in the leading journal of environmental and resource economics: the Journal of Environmental Economics and Management. Previous studies of general economic journals have offered empirical evidence for the fact that intellectual collaboration is most prevalent in the field of environmental and resource economics. However, no previous study has examined this finding more carefully. This is a gap in the literature we hope to fill. Accordingly, we investigate all 1436 papers published in JEEM from 1974 until 2010 with respect to potential drivers of co-authorship. We start with a simple descriptive analysis in order to depict the most important trends in the past 36 years. We then employ empirical methods to test several hypotheses that are commonly used to analyze the structure of co-authorship. However, we do not stick to the commonly used hypotheses but investigate also other potentially relevant drivers of co-authorship as e.g. the acknowledgment of external funding, the gender of the authors or the geographical location. We find empirical support for the rising incidence of co-authorship with increasing complexity of the field of economics and the competition for external funding. As research has become more demanding in terms of both disciplinary and - especially in the field of environmental and resource economics - interdisciplinary skills, the likelihood of collaborative research and jointly written publications increased.
urn:nbn:de:bsz:180-madoc-322926
Keywords: Q0; Q50; 330; environmental and resource economics; co-authorship; production of knowledge; Bibliometrie; Arbeitsgruppe; Umweltökonomik; Welt